Motivational Factors and Constraints of Dairy farmers trained by Krishi Vigyan Kendra - Beerannavar, Basavaraj; Raghuraja, J (Journal of Agricultural Extension Management, 2018)
The study was conducted in Shivamogga district of Karnataka state toanalyse the motivational factors, constraints and to enlist suggestions offarmers trained on dairy management practices by KVK, Shivamogga.In all 120 trained farmers from 12 villages constituted the sample forthe study. The findings revealed that the factors viz., to increase incomefrom dairy by learning new practices (76.66%), to have contact with theextension agency (55.00%), to get self-employment by attending trainingprogrammes (44.16%) motivated the respondents to attend the training.The trained farmers expressed that constraints such as, financial problems(71.67%), shortage of green fodder during summer season (59.17%), lowprice for the milk (44.17%) and inadequate veterinary services (39.17%)are adversely effecting the dairy enterprise. Majority of KVK trainedfarmers sought more number of extension activities to be organized basedon the needs of the farmers (75%), followed by, remunerative price for milk(72.50%).